Exploration of External Factors Influencing University Student Leadership Development in China’s Context - Mohan Zhang; Yan Ye (Educational Administration: Theory and Practice, 2024)
This study explores the critical factors influencing university student leadership development, focusing on external environmental variables and their impact. Leadership development has been a pivotal element in higher education for over four decades, shaping student learning outcomes, competitiveness, and self-identity. Through a review of 92 articles published in the last decade and a theoretically based quantitative study involving 813 Chinese university students from Shandong and Henan provinces, this research identifies four primary external factors affecting leadership development: leadership development activities, social environment, learning environment, and organizational interpersonal relationships. Unlike previous research, which treated external factors as a holistic influence, this study analyzes these variables individually, providing a novel perspective on their distinct contributions to student leadership development. The findings validate these factors as positive contributors to leadership growth, offering robust evidence for the significance of tailored leadership initiatives. This paper also underscores the dynamic interplay between leadership development and external environments, reinforcing their role as key success factors for leadership practices. By refining and deepening the understanding of these external factors, this research offers valuable insights for scholars and practitioners, paving the way for future studies to further enhance leadership development strategies in higher education.